(3bhGYO GdTQjYIs - (3YHO GdYRjR Hf YHO GdSdGe Hf CHj GdbGSe Hf GdMSf GdSdej GdOeTbj, YR GdOjf GdedbH HSdWGf GdYdeGA,J (B660 (3g` s ((3eOjfI WQGHdS HGdeOQSI GdTeSjI s)
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdYdGeI YRGdOjf CHh eMeO YHOGdYRjR s
(3BNQgG (B:s
(3hHYO Yf GdUhGH dGjQVi Hg MO ef Chdi GdCdHGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B21 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B249s
Keywords: (3CUhd Gdabgs